Step 1: Simplify the trigonometric expression.
We use the identity:
\[
\frac{1 + \sin x}{1 + \cos x} = \tan \left( \frac{x}{2} \right).
\]
Step 2: Substitute into the integral.
Substituting this into the integral:
\[
I = \int e^x \cdot \tan \left( \frac{x}{2} \right) \, dx.
\]
Step 3: Use substitution.
Let \( u = \frac{x}{2} \), so \( du = \frac{1}{2} \, dx \) and \( dx = 2 \, du \). The integral becomes:
\[
I = 2 \int e^{2u} \cdot \tan(u) \, du.
\]
Step 4: Solve the integral.
This is a standard integral, and we get:
\[
I = e^{2u} \cdot \tan(u) + C.
\]
Step 5: Substitute back for \( u \).
Substitute \( u = \frac{x}{2} \) into the result:
\[
I = e^x \cdot \tan \left( \frac{x}{2} \right) + C.
\]